Peripheral venous catheter colonization after skin disinfection with 0.5% aqueous sodium hypochlorite, preceded or not by one application of 70% ethanol (DACLEAN): a single-centre, randomized, open-label, pilot study. (February 2022) - Drugeon, B.; Pichon, M.; Marjanovic, N.; Mousse, S.; Seguin, S.; Raynaud, C.; Rahoui, A.; Frasca, D.; Mimoz, O.; Guenezan, J.
Summary: Few data are available on the efficacy of 0.5% aqueous sodium hypochlorite (SH) for skin disinfection before peripheral catheter insertion. A total of 239 patients were randomly assigned to either one application of SH alone or one application of SH preceded by one application of 70% ethanol (ET-SH). Catheter colonization, defined as a catheter tip culture growing >1000 cfu of a micro-organism per millilitre, occurred in 29 patients (33% of 89 colonizations per 1000 catheter-days) in the SH group and in 31 patients (33% of 126 colonizations per 1000 catheter-days) in the ET-SH group.